2007
DOI: 10.1057/palgrave.ijea.2150071
|View full text |Cite
|
Sign up to set email alerts
|

East-Asian Students' Choice of Canadian Graduate Schools

Abstract: This study seeks to explain why and how international graduate students from East Asia choose to come to Canada to pursue advanced education, to assess the strengths and dynamics of the factors infl uencing the enrollment decision, and to describe possible implications both for educationexporting countries and universities offering graduate education. A synthesis model is developed to explain their decision-making process , while a push -pull model is used to understand the strengths of and relationships among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
133
2
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(146 citation statements)
references
References 17 publications
8
133
2
3
Order By: Relevance
“…Also, he found that the reputation of the performing groups and the academic reputation of the school, the possiblity for commuting from home to school, and the friendliness of the faculty were other influencial factors. These results coincide with the results of the studies about the college choice of Asian international students in U.S. higher education institutions (Chen, 2006;Kelly, 1988;Poock & Love, 2001;Talbot, Maier, & Rushlau, 1996) in that the reputation of the programs and the faculty were the most influential factors in their college choices.…”
Section: Introductionsupporting
confidence: 81%
See 3 more Smart Citations
“…Also, he found that the reputation of the performing groups and the academic reputation of the school, the possiblity for commuting from home to school, and the friendliness of the faculty were other influencial factors. These results coincide with the results of the studies about the college choice of Asian international students in U.S. higher education institutions (Chen, 2006;Kelly, 1988;Poock & Love, 2001;Talbot, Maier, & Rushlau, 1996) in that the reputation of the programs and the faculty were the most influential factors in their college choices.…”
Section: Introductionsupporting
confidence: 81%
“…Indeed, Chen (2006) surveyed 140 East Asian international students in Canada and found that many international students in Canadian colleges or universities went to Canada because they could not obtain U.S. visas.…”
Section: Us Policy and International Studentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Foskett, Roberts, and Maringe (2006) stated the flexibility of fee payments, availability of financial aid, and reasonable accommodation costs to exert a significant influence on students' choices of a higher education institution. Chen (2007) mentioned about the internationalization activities, such as faculty exchange programs, collaborations, attending international conferences, and publishing research papers, played a crucial role in guiding these students' choice process. Alvez and Raposa (2007) listed academic excellence, job market prospects, and location as the most significant factors that determine academic choices.…”
mentioning
confidence: 99%